The World Views of the Obama Era From Hope to Disillusionment (Springer International Publishing, 2018)
This book presents selected non-US views of the Barack Obama administration. Each chapter investigates eight years of the Obama presidency from a different national perspective. By bringing together fourteen country studies from all regions of the world, this volume offers an accumulative global view of the Obama White House's foreign policies and bilateral affairs. . It provides an outside perspective on a presidency that was initially greeted with much enthusiasm world-wide, but seemed to fall out of favor over time in most countries. The overwhelming hope that was associated with the election of Obama in 2008 turned to disillusionment world-wide; the changes in US external affairs he promised were only partially fulfilled and the world was reminded that America's place and role in the world would not change dramatically, not even under the inspirational Obama.